The Privatization Dividend : A Worldwide Analysis of the Financial and Operating Performance of Newly Privatized Firms - Megginson, William L.; Nash, Robert C.; van Randenborgh, Matthias (World Bank, Washington, DC, 2012)
The study described in this Note compared the pre- and post-privatization performance of 61 companies in 18 countries and 32 industries. These companies were sold to the public through a share issue and thus their comparable pre- and post-issue financial and accounting data could be obtained from the firms' offering prospectuses and annual reports. The study tested for increased profitability, increased operating efficiency, increased capital investment spending, increased output, and privatization without lowering employment levels. It tested for these results both for the full sample and for several subsamples: privatizations of firms in competitive and non-competitive industries, full and partial privatization, privatization involving firms headquartered in OECD countries and in developing countries, and "control" and "revenue" privatizations. It showed significant increases among newly private firms in profitability, output per employee, capital spending, and employment. It also found that the financial policies of these firms start to resemble those typically associated with private entrepreneurial companies--with lower leverage and higher dividend payout ratios. Although the data did not allow precise documentation of the causes of these performance improvements after divestiture, the study was able to rule out price increases as a frequent source of profitability increases. It also showed that privatization has a positive effect on a firm's operating and financial performance while maintaining employment.